Heavily Doped Zinc Oxide with Plasma Frequencies in the Telecommunication Wavelength Range. Issue 2 (23rd December 2022) - Koch, Alexander; Mei, Hongyan; Rensberg, Jura; Hafermann, Martin; Salman, Jad; Wan, Chenghao; Wambold, Raymond; Blaschke, Daniel; Schmidt, Heidemarie; Salfeld, Jürgen; Geburt, Sebastian; Kats, Mikhail A.; et al.
Abstract : Heavy and hyper doping of ZnO by a combination of gallium (Ga) ion implantation using a focused ion beam (FIB) system and post‐implantation laser annealing is demonstrated. Ion implantation allows for the incorporation of impurities with nearly arbitrary concentrations, and the laser‐annealing process enables dopant activation close to or beyond the solid‐solubility limit of Ga in ZnO. Heavily doped ZnO:Ga with free‐carrier concentrations of ≈10 21  cm −3, resulting in a plasma wavelength of 1.02 μm, which is substantially shorter than the telecommunication wavelength of 1.55 μm is demonstrated. Thus, this approach enables the control of the plasma frequency of ZnO from the far infrared down to 1.02 μm, thus, providing a promising plasmonic material for applications in this regime. Abstract : The optical properties of ZnO are tunable by Gallium ion implantation and laser annealing. The highest achieved free‐carrier concentration in ZnO:Ga is N e  ≈ 1.23 ± 0.41 ×10 21  cm −3 . Heavily doped ZnO:Ga by a focused ion beam (FIB) opens a wide field for lateral arrangements of doped and un‐doped regions, which are a promising for photonic or plasmonic applications.